Therapeutic itinerary of severe malaria in adults admitted to a teaching hospital in Dakar, Senegal - Sylvie Audrey Diop; Cossi Angelo Attinsounon; Louise Fortes-Deguenonvo; Viviane Marie Pierre Cisse Dialo; Moussa Seydi (Journal of Infection in Developing Countries)
Introduction: Despite prevention efforts, malaria remains a public health problem. Methodology: This was a prospective study conducted between October and December 2010 that aimed to describe the therapeutic route of adults presenting with severe malaria prior to being admitted to Fann Teaching Hospital in Dakar, Senegal. Results: A total of 90 patients were included. The majority of them had consulted a public or private health care facility (92%) prior to admission. First consultation occurred on average two days after the onset of the disease. Self-medication (67.4%) and traditional medicine (26.1%) were the main causes of delaying care. Conclusions: Early care and adequate management are needed to reduce malaria mortality.